Necesidad de reformar el código de ejecución de penas y rehabilitación social con la finalidad de hacer efectivo el cumplimiento del objetivo de la ley en cuanto a la reinserción laboral del reo - Gavilanes Gavilanez, Ana María (2014)
One of the rules for the prison location as stated in Article 21 of the Code of Execution of Sentences and Social Rehabilitation, stating that the population location and treatment of inmates held by the progression system in accordance with this Act and regulations, in social rehabilitation centers and base, in paragraph 2 letter c) in the centers of social rehabilitation of medium security: mandatory and regulated work with job training; in paragraph 3 letter c) In social rehabilitation centers minimum security: The work, which shall be binding and self-regulated, with employment promotion and training. Section 37 of the Code of Execution of Sentences and Social Rehabilitation indicates that for the implementation of the treatment periods interned for criminal criminological study and classification, sales, pre-release, controlled release treatment population and location in each of the social rehabilitation centers will be established in the following departments: a) diagnosis and evaluation; b) Assistance; and, c) Labor. But the fact is that there is effective compliance object of the law regarding the reintegration of the offender, so that Article 48 of the Code of Execution of Sentences and Social Rehabilitation states that assistance released is a function state that will be fulfilled through the appropriate department, which will aim to ensure that the released can reintegrate into society, and do so in conditions allowing for a harmonious development in it. This objective will be met by medical psychiatric, labor and community , and through the warranty set forth in the following assistance. Regarding the labor system in need of government support for their reintegration, such as the National Development Bank loans to stretch out or sentenced Rehabilitation Centers in the country proposed micro form, woodworking, metalworking, seamstress and beauty with order to make a real social rehabilitation. In our country the prison policy is determined by the Constitution of the Republic of Ecuador, the Penal Code and Code of Execution of Sentences and the latter by the rules and procedures of the different specialties involved in prison work, in terms of treatment and rehabilitation; all problems relating to the effectiveness and prison education system is in Ecuador renovators care pathways for human betterment. For this circumstance, to enforce compliance regarding the reintegration of prisoners, that the formation of micro is allowed in order to rehabilitate not only the internal but create jobs for and sentenced.